1986
DOI: 10.1203/00006450-198602000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Thymidine Kinase Activity in Man

Abstract: ABSTRACT. Thymidine kinase activity was studied during human adipose tissue development. Adipose tissue was obtained from the groin in 81 persons, aged 7 wk through 60 yr. None had a metabolic or growth disorder. Adipose tissue thymidine kinase activity was highest in infants and lowest in adults. Peak thymidine kinase activity was seen in the early postnatal period and a lesser elevation was found in the preadolescent years, coinciding with hypothesized periods of proliferation of preadipocytes in man. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…This may reflect a chance finding, or different maternal characteristics in the two cohorts, such as the greater maternal adiposity and maternal folate supplementation in the SWS cohort (22,40,41). Alternatively, adipocyte proliferation is high during the first year of life, but then remains low until a second proliferate phase from 9-14 years (42). Thus the processes which determine adiposity at 9 years might differ from those at 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect a chance finding, or different maternal characteristics in the two cohorts, such as the greater maternal adiposity and maternal folate supplementation in the SWS cohort (22,40,41). Alternatively, adipocyte proliferation is high during the first year of life, but then remains low until a second proliferate phase from 9-14 years (42). Thus the processes which determine adiposity at 9 years might differ from those at 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies favour the view that, during the first year of life, body fat accumulates through an increase of mean adipocyte size (hypertrophy), a characteristic feature of body fat increase (9,10). Other studies have also shown a sudden proliferation of (presumably) precursor cells in the subcutaneous adipose tissue of infants during the first year of life (11,12). As the number of adipocytes increases with the early onset of childhood obesity (13), it is reasonable to assume that the capacity of precursor cells to divide and to undergo possible self‐renewal is highest during the first year of life regardless of their differentiation into adipocytes taking place at that time or later in life.…”
Section: White Adipose Tissue Development In Early Lifementioning
confidence: 99%
“…The enlargement of adipose tissue during its first rapid growth in the first year of life seems to be mainly due to an increase in the volume of already existing fat cells [7][8][9], More recent studies provide evi dence that the proliferation of adipocyte precursor cells may also be stimulated during this period [10,11]. From the end of the first year of life fat cell size in normalweight individuals seems to remain almost stable [7], The further growth of the adipose organ is probably due to an augmentation of fat cell number, especially evident dur ing its second period of rapid growth before and during puberty [7],…”
Section: Development Of Adipose Tissue In Normal Childrenmentioning
confidence: 99%